1998
DOI: 10.3168/jds.s0022-0302(98)75644-9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Supplemental Fats on Reproductive Tissues and Performance of Lactating Cows

Abstract: Fat supplementation (about 3% of dietary dry matter) has often positively influenced the reproductive status of the dairy cow, including increased size of the ovulatory follicle, increased numbers of ovarian follicles, increased plasma concentration of progesterone, reduced secretion of prostaglandin metabolite, increased lifespan of the corpus luteum, and improved fertility. Supplemental fat may allay partially negative energy status during the early postpartum period, yet often the positive reproductive infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
265
4
54

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 376 publications
(330 citation statements)
references
References 93 publications
7
265
4
54
Order By: Relevance
“…Although numerous studies have advanced knowledge of the influence of fat and mix of fatty acids on oocyte developmental competence [9][10][11][12][13], data on the effect of each family or each specific fatty acid are rare and the results of the existing studies are somewhat discordant. All-cis-9,12,15-octadecatrienoic acid or α-linolenic acid (ALA,18:3 n-3, an essential fatty acid of the ω-3 family) is a PUFA highly abundant in some vegetable oils and sea fishes [14].…”
Section: Introductionmentioning
confidence: 99%
“…Although numerous studies have advanced knowledge of the influence of fat and mix of fatty acids on oocyte developmental competence [9][10][11][12][13], data on the effect of each family or each specific fatty acid are rare and the results of the existing studies are somewhat discordant. All-cis-9,12,15-octadecatrienoic acid or α-linolenic acid (ALA,18:3 n-3, an essential fatty acid of the ω-3 family) is a PUFA highly abundant in some vegetable oils and sea fishes [14].…”
Section: Introductionmentioning
confidence: 99%
“…With low concentrations of insulin, the secretion of the hormonesensitive lipase is stimulated, increasing lipolysis with the subsequent release of NEFA to the bloodstream (Melendez et al, 2009). According to Staples et al (1998), plasma insulin concentrations reflect the energy intake. In our study, insulin is not reflecting energy intake in early lactation, but LD = lower energy density; HD = high energy density; S = strategy; P = parity; DMI R 1 = DMI of the partially mixed rations (LD and HD); DMI C 2 = DMI of the concentrates at the milking robot; WIM = weeks in milk; SCC = somatic cell counts.…”
Section: Discussionmentioning
confidence: 99%
“…Cis-linoleic acid (18:2n-6) can be desaturated and elongated to form dihomo-γ-linolenic acid which serves as an immediate precursor for series one PG or can be desaturated further to arachidonic acid (20:4), an immediate precursor for series two PG [23]. Although not apparent in the present study, linoleic acid may also exert inhibitory effects on PG synthesis by competing with arachidonic acid for binding to cyclooxygenase [23]. Staples et al [23] suggested the amount of particular fatty acids reaching the target tissues likely influence whether PG synthesis is stimulated or inhibited.…”
Section: Discussionmentioning
confidence: 99%